One-Dimensional Nonequilibrium Radiation-Transport Equation under Diffusion Approximation and Its Discrete Scheme - Qi Gao; Chuanfei Zhang; Lin Zhou; Zhenghong Li; Zeqing Wu; Yu Lei; Chunlai Zhang; Xiaotao Zu (Advances in Condensed Matter Physics)
Based on the nonlocal thermodynamic equilibrium state and large optical thickness of plasma, we establish one-dimensional nonequilibrium radiation-transport equation from diffusion approximation. Through finite volume method, the discrete scheme of radiation-transport equation and the conditions for its definite solution are proposed. The reliability of radiation-transport equation and its discrete scheme is validated.